The Global Cohort of Doctoral Students: Building Shared Global Health Research Capacity in High- Income and Low- and Middle-Income Countries - Semira Abdelmenan; Christopher T. Andersen; Fentabil Getnet; Hari S. Iyer; Kesaobaka Molebatsi; Simone Passarelli; Sara M. Sauer; Muhammed Semakula (Ubiquity Press, 2021)
Doctoral students in high- and low-income countries pursuing careers in global health face gaps in their training that could be readily filled through structured peer-learning activities with students based at partnering institutions in complimentary settings. We share lessons learned from the Global Cohort of Doctoral Students, a community of doctoral students based at the Harvard T. H. Chan School of Public Health, Haramaya University, University of Gondar, University of Botswana, and University of Rwanda College of Medicine and Health Sciences. Students in the Global Cohort program engage in collaborative research, forums for constructive feedback, and professional development activities. We describe the motivation for the program, core activities, and early successes.